Variation of clinical features in COVID-19: A narrative review - Bhusal, Laxman; Bom, Rabin; Devkota, Dibya (Journal of General Practice and Emergency Medicine of Nepal, 2020)
Introduction: COVID-19 is global pandemic condition caused by severe acute respiratory syndrome Coronavirus 2 (SARS-CoV-2) which started in December in China, affecting 216 countries till date. Lack of experience and diverse clinical features of this virus is alarming to scientists and health personals.Method: Systemic review search conducted using pub med, google scholar, WHO and CDC. Search was done using terms Coronavirus, clinical features, 2019-nCoV, SARS-CoV-2, SARS-CoV, MERSCoV and COVID-19. COVID-19 or SARS-Cpv-2 related original English literature research, review articles, case reports, meta-analysis and systemic review were included.Result: Having higher infectivity of COVID-19 compared to previous epidemics of coronavirus, droplet transmission occurs both from symptomatic and asymptomatic patients. Aerosol transmission occurs in protracted exposure to elevated concentrations of virus. Besides fever, cough and SOB, GI symptoms like nausea, vomiting and diarrhoea were seen. Anosmia is evolving as new clinical feature. Increased thrombotic complications in critically ill patients were pronounced. Most cases were mild with low case fatality rate ranging from 2.3-7.2% among critical patients.Conclusion: Despite recent advances and increasing studies, the global pandemic COVID-19 still remains major headache and challenging for governments across the world due to limited testing capacity, treatment and vaccine.